2020
DOI: 10.1155/2020/6513246
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Intimate Partner Violence and Associated Factors among Victimized Women, Ethiopia, 2018: A Community-Based Study

Abstract: Background. Disclosure is a vital step in the process of finding a lasting solution and breaking the abuse chain in a victim woman by the intimate partner. Objectives. This study is aimed at assessing the disclosure of intimate partner violence and associated factors among victim women in Dilla town, Gedeo Zone, South Ethiopia, 2018. Methods. A community-based cross-sectional study design triangulated with the qualitative method was employed. Data were collected from 280 women victims of intimate partner viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
(44 reference statements)
3
12
2
Order By: Relevance
“…The prevalence of postpartum IPV (31.4%) in this study was comparable with the study done in United States (33.8%), Brazil (25.6%), and Beijing, China (32.5%). 5 , 8 , 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of postpartum IPV (31.4%) in this study was comparable with the study done in United States (33.8%), Brazil (25.6%), and Beijing, China (32.5%). 5 , 8 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…A structured questionnaire was prepared after a detailed review of the literature of different studies. 3 , 5 , 6 , 10 , 14 16 , 19 , 23 Sociodemographic characteristics, reproductive characteristics, and behavior of women and her partner-related characteristics were all included in the questionnaire. The tool reliability test was checked by Cronbach’s alpha, which indicated that 0.79.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of guidelines at care services sites can be linked with lack of nancial and human resources suitably quali ed and committed to addressing the DV-related issues,compromising adequate implementation as well as monitoring and evaluation of national strategies [28,30,34,35]. Simultaneously, the low quali cation of professionals providing care to survivors of DV is in uenced by negative socio-cultural factors and demographic characteristics such as sex and age [36][37][38].These factors undermine the non-judgmental, empathetic, and understandable approach [39,40].The lack of nancial and human resources can also be co-substantiated by the fact that CSOs, where funding does not depend on general state funds, frequently design and disseminate DV prevention and control messages. Another example of the lack of government investment, is the existence of guidelines co-nanced by a CSO.…”
Section: Discussionmentioning
confidence: 99%
“…Also, disclosure can be one of the means of survival from violence [5]. Most frequently mentioned factors in previous studies as the reason behind non disclosure of intimate partner violence to others were economic and socio-political discrimination of women, being dependent on partners' income, the severity of the violence, those who are severely violated more likely to disclose their experience to the formal social services, stress, accepting violence as normal, concerns about bringing bad name to the family, lack of confidence, shame/embarrassment/fear of getting blamed, fear for children's future life, women who were unemployed and pregnant, and lack of encouragement by family members and educational status [6].…”
Section: Introductionmentioning
confidence: 99%